1991
DOI: 10.1037/0021-843x.100.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of children of alcoholics: Putative risk factors, substance use and abuse, and psychopathology.

Abstract: A sample of 253 children of alcoholics (COAs) and 237 children of nonalcoholics (non-COAs) were compared on alcohol and drug use, psychopathology, cognitive ability, and personality. COAs reported more alcohol and drug problems, stronger alcohol expectancies, higher levels of behavioral undercontrol and neuroticism, and more psychiatric distress in relation to non-COAs. They also evidenced lower academic achievement and less verbal ability than non-COAs. COAs were given Diagnostic Interview Schedule alcohol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
655
8
13

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 829 publications
(728 citation statements)
references
References 86 publications
52
655
8
13
Order By: Relevance
“…The clinical details of the 14-17 year olds is tabulated in the Table 1. The samples were matched for age, but not matched on drug use and other Axis I conditions since the reported rates for some conditions in subjects with family history of alcoholism are elevated over normal population levels (Cuijpers et al, 1999;Nurnberger et al, 2004;Sher et al, 1991). The sample of the present study differs from most published high risk studies with respect to the following point -The status of alcoholism in all the index subjects and their first-degree relatives have been diagnosed and confirmed by individual assessment using the SSAGA, and corroborated with the family history assessment module (FHAM).…”
Section: Sample Used In the Present Studymentioning
confidence: 99%
“…The clinical details of the 14-17 year olds is tabulated in the Table 1. The samples were matched for age, but not matched on drug use and other Axis I conditions since the reported rates for some conditions in subjects with family history of alcoholism are elevated over normal population levels (Cuijpers et al, 1999;Nurnberger et al, 2004;Sher et al, 1991). The sample of the present study differs from most published high risk studies with respect to the following point -The status of alcoholism in all the index subjects and their first-degree relatives have been diagnosed and confirmed by individual assessment using the SSAGA, and corroborated with the family history assessment module (FHAM).…”
Section: Sample Used In the Present Studymentioning
confidence: 99%
“…Personality variation has also been implicated in the diathesis for alcohol dependence. Several characteristics have been suggested including negative affectivity and neuroticism [see Sher and Trull, 1994 for review], alienation [Hill et al, 1990b], and disinhibition/impulsivity [Sher et al, 1991] in offspring of alcoholics. We have found higher scores on the extraversion scale of the Eysenck Personality Inventory (EPI) predicts adolescent age of onset to begin regular drinking among high-risk offspring [Hill and Yuan, 1999;Hill et al, 2000b].…”
Section: Introductionmentioning
confidence: 99%
“…This is a serious limitation of the COA literature because many studies have shown that comorbid psychiatric problems such as depression, anxiety, drug dependence, and antisocial personality disorder frequently occur among both community dwelling and treated alcoholics (Hill & Hruska, 1992;Kessler et al, 1994;Penick et al, 1994;Sher, Walitzer, Wood, & Brent, 1991;Tarter, 1988;Windle & Searles, 1990). For example, it is estimated that 47% of alcoholics from the community have a comorbid psychiatric diagnosis (Helzer & Pryzbeck, 1988).…”
mentioning
confidence: 99%